The Specter of Revealed Preference Theory - Lukas Beck (Ergo, An Open Access Journal of Philosophy, 2024)
My aim in this paper is to argue that the recent philosophical defenses of revealed preference theory do not withstand scrutiny. Towards this aim, I will first outline revealed preference theory. I will then briefly present the two most common arguments that the received view offers against it. Afterwards, I will outline three argumentative strategies for rehabilitating revealed preference theory, and successively rebut each of them.